Self-Compassion Training Can Reduce Self Injury in Adolescents, Is It Effective? - Ramadani, Nur Fitri; Murdiana, Sitti (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
This study aims to determine the effectiveness of self-compassion training for lowering self-injury in teenagers. The amount of participants in this study is 16 teenagers which are divided into two groups, namely the control group and the experimental group. The experimental design in this study is a two-group pretest-posttest design. The data analysis technique used in this research is the Mann-Whitney test and additional analysis using the Wilcoxon test with the help of the SPSS 26 program for Windows. Based on the results of the hypothesis test using the Mann-Whitney U test, a significance value of p = 0.003 (p <0.05) is obtained which means the hypothesis in this study is accepted, namely self-compassion training is effective for reducing self-injury in teenagers. Furthermore, the results of the Wilcoxon test obtained a significance value of p = 0.012 (p <0.05), which means that there is a significant difference between the experimental group and the control group in decreasing self-injury. The update in this study compared to previous studies is the direct administration of self-compassion in the form of training to see the effect on reducing self-injury. In addition, individuals can increase self-compassion using three types of training, namely mirror talk, loving-kindness meditation, and letters of me which have been proven effective in reducing self-injury.Penelitian ini bertujuan untuk mengetahui efektivitas pelatihan self-compassion dalam menurunkan self injury pada remaja. Partisipan penelitian berjumlah 16 orang remaja yang dibagi dalam dua kelompok, yaitu kelompok kontrol dan kelompok eksperimen. Rancangan eksperimen dalam penelitian ini adalah two-group pretest-posttest design. Teknik analisis data yang digunakan dalam penelitian ini adalah uji Mann-Whitney dan analisis tambahan menggunakan uji Wilcoxon dengan bantuan program SPSS 26 for windows. Berdasarkan hasil uji hipotesis menggunakan uji Mann-Whitney U diperoleh nilai signifikansi p=0,003 (p<0,05) yang artikan hipotesis dalam penelitian ini diterima, yaitu pelatihan self-compassion efektif dalam menurunkan self injury pada remaja. Sedangkan hasil analisis uji Wilcoxon diperoleh nilai signifikansi p=0,012 (p<0,05) yang artinya ada perbedaan yang signifikan pada kelompok eksperimen dan kelompok kontrol dalam penurunan self injury. Keterbaruan dalam penelitian ini dibandingkan penelitian terdahulu adalah pemberian secara langsung self-compassion dalam bentuk pelatihan untuk melihat efek dalam penurunan self injury. Selain itu, individu dapat meningkatkan self-compassion menggunakan tiga jenis pelatihan yaitu mirror talk, meditasi loving-kindness, dan letter of me yang terbukti efektif dalam menurunkan self injury.